Pemberdayaan Anggota PKK Kelurahan Kauman Kota Malang dalam Pembuatan Lilin Aromaterapi - Ani Riani Hasana; Wibowo (Yayasan Inspirasi El Burhani, 2023)
Introduction: This Community Service Activity begins with an initial assessment of the situation in the field. The initial study found problems from the results of a preliminary study conducted by interviewing elderly people who experienced insomnia in Kauman Village, Malang City, as many as 10 elderly people who experienced insomnia. Objective: This community service activity aims to provide knowledge related to making aromatherapy candles. Method: The implementation of this activity begins with the process of evaluating the level of knowledge and attitudes of PKK cadres regarding the prevention stress and how to make of aromatherapy candles by conducting a pre-test using a questionnaire. Then, the team provided education about the prevention stress and how to make of aromatherapy candles by using appropriate media. This activity was carried out using the transfer & sharing method of knowledge by using aids of audiovisual media and leaflets, and practice of making aromatherapy candles. Besides being open for discussion sessions, questions, and answers related to aromatherapy candles. Result: The success of the PkM program can be seen from this. This can be seen from the average increase in understanding ability to 33.57%. The pretest average value of the 23 PkM participants was 65.2% and after participating in the PkM activities the understanding of the activity participants obtained the posttest average value of the 23 PkM participants was 98.3%. Then from the results of the evaluation of the skills of the participants, a value of 86.67 was obtained and could be categorized as skilled. Conclusion: We concluded that providing education related to how to make aromatherapy candles could increase people's knowledge and attitudes.